Twin-like fault in Mg–9.8 wt%Sn alloy. (October 2018) - Liu, Chaoqiang; Chen, Houwen; Wilson, Nick; Nie, Jian-Feng
Abstract: Stacking faults in magnesium alloys have received considerable attention in recent years, but only intrinsic and extrinsic faults are studied at experimental and computational levels. Twin-like fault, designated as T2 fault, has received little attention. In this study, we report for the first time the occurrence of T2 fault in Mg–9.8 wt%Sn alloy. The T2 fault and solute segregation in regions surrounding the fault were characterized using aberration-corrected scanning transmission electron microscopy and first-principles calculations. Sn atoms orderly distribute in the fault plane and its neighbouring planes, which drastically decreases the T2 fault energy. Graphical abstract: Unlabelled Image